Homeowner Fact Sheet: Citrus Canker - Megan M. Dewdney; Mongi Zekri; Jamie D. Burrow; Pamela D. Roberts (EDIS, 2018)
Citrus cankers is a serious disease of all citrus cultivars and some citrus relatives, but is not harmful to humans and other animals. It is an introduced disease in Florida and is very economically damaging to the commercial industry. This disease is of concern to homeowners also, not only because of its economic effects on the  commercial industry, but because it is highly contagious and the majority of infected fruit on a severely affected tree may drop off the tree prematurely. This 4-page fact sheet is a minor revision written by M. M. Dewdney, M. Zekri, P. D. Roberts, and J. D. Burrow, and published by the Plant Pathology Department, May 2018.